1986
DOI: 10.1530/acta.0.1110030
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of intensive plasma exchange followed by immunosuppressive therapy in severe Graves' ophthalmopathy

Abstract: Nine patients with severe Graves' ophthalmopathy were treated by intensive plasma exchange, followed by immunosuppression. Severity of ocular involvement and response to therapy were evaluated clinically by numerical scoring (ophthalmopathy index). Serum thyroid stimulating immunoglobulins (TSI) and urinary excretion of glycosaminoglycans (GAG) were measured immediately before and immediately after plasmapheresis.Plasma exchange was rapidly accompanied by marked clinical improvement in 8/9 patients. The most m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…The patients were submitted to 4 plasmapheresis sessions over a period of 5-8 days and were subsequently treated for 3-6 months with a combination of prednisolone and azathioprine; three patients had a recurrence of ophthalmopathy 1 yr after treatment, requiring a second course of plasmapheresis (153). Favorable results were also reported by Berlin et al (154), who observed a reduction of the OI in 9 (69%) and of subjective symptoms in 10 (77%) of 13 patients; azathioprine was concomitantly administered to 8 patients, and 2 patients needed further sessions of plasmapheresis.…”
Section: Plasmapheresismentioning
confidence: 99%
“…The patients were submitted to 4 plasmapheresis sessions over a period of 5-8 days and were subsequently treated for 3-6 months with a combination of prednisolone and azathioprine; three patients had a recurrence of ophthalmopathy 1 yr after treatment, requiring a second course of plasmapheresis (153). Favorable results were also reported by Berlin et al (154), who observed a reduction of the OI in 9 (69%) and of subjective symptoms in 10 (77%) of 13 patients; azathioprine was concomitantly administered to 8 patients, and 2 patients needed further sessions of plasmapheresis.…”
Section: Plasmapheresismentioning
confidence: 99%
“…It is considered that the present therapy was more effective than others [14]. Although extraocular muscle dysfunction in particular has been considered to be refractory to other therapies [5,10,27,32], it is reported that 60% [18] or 75% [20] of patients showed a loss of diplopia with steroid pulse therapy.…”
Section: Resultsmentioning
confidence: 89%
“…TAO seems to be caused by an autoimmune mechanism related to the thyroid [2][3][4]. Various immunosuppressive therapies have been reported, including systemic steroids [5], retrobulbar steroids [6], azathioprine [7], cyclophosphamide [8], cyclosporine [9,10], plasmapheresis [11,12], high-dose immunoglobulin [13] and combinations thereof [14,15]. Although high-dose systemic corticosteroids, e. g. prednisolone 80-100 mg daily, have been used with some success, there is a high tendency to relapse as the steroid doses are reduced and often maintenance levels of 30 mg per day or more are needed, which leads an increase in the frequency and severity of adverse effects [16].…”
mentioning
confidence: 99%
“…In our case, for example, the best response to TPE was in a patient with a non-autoimmune disease. The success of TPE in this case was attributed to the dilution of hormones and the generation of free proteins with new binding sites, which reduced their free fractions and thus their biological activity [15][16][17][18][19][20][21]. While this is effective in the short-term, its effect is transient and so TPE cannot be used as definitive therapy.…”
Section: Discussionmentioning
confidence: 99%